The model of training specialists for state and municipal services using state information systems - A. O. Bidzhiev (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. In the conditions of rapidly developing and extensive implementation of digital technologies, it relevant for state and municipal employees to master professional competences in terms of working with state information systems and digital services that can significantly increase the efficiency of solving problems faced by specialists in the sphere of state and municipal administration.Goal. The paper aims to develop an optimal training model for the course on state and municipal administration using the means of state information systems.Materials and methods. The research is based on the analysis of the requirements set by the modern system of state and municipal administration to the its specialists.Results and discussion. In the course of the research the structure of the model of training state and municipal employees with the use of state information systems and digital services is defined. The structural elements of this model are described sequentially.Conclusion. According to the results of the study, we can conclude that the model should be formed in a concise manner and consist of the following integral components: the definition of professional competencies of public and municipal employees using digital services in their activities; the development of training programmes; the organization of placement; certification and attestation; opportunities for continuous development. Consistent development of each of the components will make it possible to construct the described model in the most efficient way and, as a result, to create an effective mechanism for preparing highly qualified state and municipal employees who are ready to work and develop in a frequently changing environment.